(3YQa GdWjH ef CNHGQ ecI heOjfI GdMHjHs - (3GHf GdYGbhdj , eMeO Hf eMeO Hf YHO Gddg GdhGSWj GdHZOGOj, ZjGK GdOjf CHh GdecGQe,J (B797 (3g` s
(3ChdgG (B:s
(3hHYO aEf cJGHfG gPG eTJed Ydi NdGUI cJGH CHj GdhdjO GdCRQbi, hLGeY GdCUhd deLO GdOjf GdeHGQc Hf GdCKjQ GdLRQi ef CMhGd GdHjJ GdMQGe s
(3BNQgG (B:s
(3bGd QShd Gddg Udi Gddg Ydjg hSde(B: (3ZdX GdbdhH hGdLaG ef GdeTQb hGdEjeGf aj Cgd GdMLGR CNQLg eSde s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B43 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B240s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JQGjN (B- (3bSe (B4 - (3U (B287 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs